Arcadie : revue littéraire et scientifique ; vanaf 22(1975) 261 : mouvement homophile de France. (Paris : Arcadie, 1954)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 162 rue Jeanne-d'Arc, Paris-13e ; vanaf 07(1960) ? : 74 Boulevard de Reuilly, Paris-12e ; vanaf 11(1964) ? : 19 rue Béranger, Paris-3e ; vanaf 17(1970) ? : 61 rue du Château-d'Eau, Paris-10e
Frans
Periodiek